Faktor-faktor yang Mempengaruhi Implementasi Kebijakan Ruang Terbuka Hijau di Kabupaten Rembang - Meidian Miranti; Sundarso Sundarso; Hartuti Purnaweni (Journal of Public Policy and Management Review, 2015)
Environmental imbalance caused as more demand than available land designated as green areas is an important note to Rembang Regency to create policies that focus on how to balance the environment. Green Open Space Policy in Rembang refer to Regulation No. 14 of 2011 on Rembang Spatial Planning. The existence of specific policies for protected areas and open green spaces in urban areas in Rembang also listed in Rembang spatial policy. Qualitative descriptive method is the method used in this study, to determine the factors driving and inhibiting in the implementation of Green Open Space Policy in Rembang using the theory of George C. Edwards III, covering four factors: Communication, Resources, Disposition, and Bureaucratic Structure. The result showed that the Green Open Space Policy in Rembang able to increase the supply, regulation and maintenance of green open space. KBT Marine Parks, Parks Borotugel, Mondoteko Park and updating of Rembang City Square are growing evidence of consistency in the government in meeting the 30% that has been mandated for green space. Research in the Green Open Space Policy implementation in Rembang recommends: (1) Sharing the determination of budget between Parliament and related implementing agencies in order to 2 adapt the needs the budget; (2) Provision of seeds in support of NGOs and community greening program; and (3) Increasing public participation in the development and management of green space.